2009
DOI: 10.1086/605087
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Universal Influenza Immunization on Antibiotic Prescriptions: An Ecological Study

Abstract: The Canadian province of Ontario introduced universal influenza immunization in 2000, offering free vaccines to the entire population. We compared changes in rates of influenza-associated respiratory antibiotic prescriptions before and after universal immunization in Ontario with corresponding changes in other provinces. Universal influenza immunization is associated with reduced influenza-associated antibiotic prescriptions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(69 citation statements)
references
References 17 publications
2
66
0
1
Order By: Relevance
“…34 A study conducted in Canada demonstrated convincingly that influenza associated antibiotic prescriptions declined by ∼64% after introduction of universal influenza vaccination in Ontario compared to other Canadian provinces that limited the use of influenza vaccines to populations most at risk for disease. 35 The second mechanism by which viral vaccines can reduce AMR is by prevention of inappropriate antibiotic prescriptions for respiratory tract infections caused by viral pathogens. For example, in the US half of all antibiotic prescriptions are inappropriately written for respiratory illnesses associated with pathogens such as influenza, respiratory syncytial virus (RSV) and other viruses that are not susceptible to antibiotics.…”
Section: Impact Of Viral Vaccines On Amrmentioning
confidence: 99%
“…34 A study conducted in Canada demonstrated convincingly that influenza associated antibiotic prescriptions declined by ∼64% after introduction of universal influenza vaccination in Ontario compared to other Canadian provinces that limited the use of influenza vaccines to populations most at risk for disease. 35 The second mechanism by which viral vaccines can reduce AMR is by prevention of inappropriate antibiotic prescriptions for respiratory tract infections caused by viral pathogens. For example, in the US half of all antibiotic prescriptions are inappropriately written for respiratory illnesses associated with pathogens such as influenza, respiratory syncytial virus (RSV) and other viruses that are not susceptible to antibiotics.…”
Section: Impact Of Viral Vaccines On Amrmentioning
confidence: 99%
“…Others do so indirectly. The influenza vaccine, for instance, cuts the incidence of fevers, and so minimizes the number of antibiotic doses that are needlessly prescribed and taken 10 . We call for a global strategic effort to develop a portfolio of vaccines that target AMR.…”
Section: Vaccines For Amrmentioning
confidence: 99%
“…While it is within the scope of practice to prescribe antibiotics to treat these infections, prior immunization with the viral influenza vaccine can prevent secondary bacterial infections and thereby reduce the need for antibiotic usage. For example, in a Canadian study, the introduction of universal influenza vaccination, resulted in a 64% decrease in influenza associated respiratory disease antimicrobial prescriptions in the province of Ontario [92]. This effect has been corroborated by others [93].…”
Section: Value Of Conjugated Vaccine Technologiesmentioning
confidence: 58%